Underweight increases the risk of pulmonary tuberculosis in adult - Irawan, Galuh Chandra; Margawati, Ani; Rosidi, Ali (Universa Medicina, 2017)
BackgroundTuberculosis (TB) is a leading cause of morbidity and mortality, especially in middle- and low-income countries. The risk of developing TB may be related to nutritional status. Socioeconomic and behavioral factors are also shown to increase the susceptibility to TB infection.Â The objective of this study was to determine nutritional factors as risk factors of pulmonary TB in adult.MethodsThis was an observational study of case control design. The study subjects were community members consisting of 19 adult cases of pulmonary tuberculosis and 38 controls. Data on nutritional intakes were obtained by semiquantitative food frequency questionnaire (FFQ), while smoking behavior, history of DM, body mass index, education, and income were obtained by structured interviews. The data were analyzed by independent t-test and logistic regression for calculation of the odds ratio (OR).ResultsThe bivariate test showed that the adequacy levels for energy (OR=6.8; 95% CI: 1.51-30.54), protein (OR=5.1; 95% CI: 1.52-17.14), vitamin A (OR=4.2; 5% CI: 1.31-13.54), vitamin C (OR=3.8;95% CI: 1.21-12.36), selenium (OR=4.2; 95% CI: 1.34-13.58), body mass index (OR=4.4; 95% CI: 1.32-14.35) and smoking behavior (OR=3.7; 95% CI: 1.15-11.9), were significant risk factors for pulmonary tuberculosis. Multiple logistic regression test showed that low body mass index (<18.5 kg/m2) (OR=6.0; 95% CI: 1.32-27.18) was a the most influential risk factor of pulmonary tuberculosis.ConclusionLow body mass index is the most influential risk factor for pulmonary tuberculosis incidence in adult. Nutrition profile in adult is an important determinant of TB incidence.